Serum Alpha-1-Acid Glycoprotein-1 and Urinary Extracellular Vesicle miR-21-5p as Potential Biomarkers of Primary Aldosteronism - Carvajal, Cristian A.; Tapia-Castillo, Alejandra; Pérez, Jorge A.; Fardella, Carlos E. (Frontiers in Immunology, 2021)
Primary aldosteronism (PA) is the most common cause of secondary hypertension and reaches a prevalence of 6-10%. PA is an endocrine disorder, currently identified as a broad-spectrum phenotype, spanning from normotension to hypertension. In this regard, several efforts have been done to advance in the identification of mediators and novel biomarkers of PA as specific proteins, miRNAs, and lately extracellular vesicles (EVs) and its cargo. Aim: To evaluate lipocalins LCN2 and AGP1, and specific urinary EV miR-21-5p and Let-7i-5p as novel biomarkers for PA. Subjects and Methods: A cross-sectional study performed in 41 adult subjects classified as normotensive controls (CTL), essential hypertensives (EH), and primary aldosteronism (PA) subjects, similar in gender, age and BMI. Systolic (SBP) and diastolic (DBP) blood pressure, aldosterone, plasma renin activity (PRA), and aldosterone to renin ratio (ARR) were determined. Inflammatory parameters as hs-C reactive protein (hs-CRP), PAI-1, MMP9, IL6, LCN2, LCN2-MMP9 and AGP1. We isolated urinary EVs (uEVs) and measured two miRNA cargo miR-21-5p and Let-7i-5p by Taqman-qPCR. Statistical analyses as groups comparison was performed by Kruskall-Wallis, and discriminatory analyses by ROC curves were performed with SPSS v21 and Graphpad-Prism v9. Results: PA and EH subjects have significant higher SBP and DBP (p <0.05) than control group. PA subjects have similar hs-CRP, PAI-1, IL-6, MMP9, LCN2, LCN2-MMP9 but have higher levels of AGP1 (p <0.05) than CTL&EH group. Concentration and size of uEVs and miRNA Let-7i-5p did not show any difference between groups. In PA, we found significant lower levels of miR-21-5p than controls (p <0.05). AGP1 was associated with aldosterone, PRA and ARR. ROC curves detected AUC for AGP1 of 0.90 (IC 95 [0.79 – 1.00], p <0.001), and combination of AGP1 and EV-miR-21-5p showed an AUC of 0.94 (IC 95 [0.85 – 1.00], p<0.001) to discriminate the PA condition from EH and controls. Conclusion: Serum AGP1 protein was found increased, and miR-21-5p in uEVs was decreased in subjects classified as PA. Association of AGP1 with aldosterone, renin activity and ARR, beside the high discriminatory capacity of AGP1 and uEV-miR-21-5p to identify the PA condition, place both as potential biomarkers of PA.